ITERATIVE ALGORITHMS OF SEARCHING NUMBERS WITH FIXED FREQUENCY OF THEIR SYMBOLS (Journal of Information Technologies in Education (ITE), 2015)
Every numbering system has its own alphabet, which is used for symbolic representation of a number. Historically, the first system for representation of real numbers was s-adic numbering system (1
Keywords: s-adic representation of numbers; frequency of symbol; normal number; Iterative algorithm; software; elective course